Analysis of Changes in Inflammatory Factor Levels and Pregnancy Rate in the Treatment of Endometritis with Guizhi Fuling Decoction Combined with Metronidazole (Journal of research in medical and health sciences, 2026)
Objective This study aims to investigate the impact of Guizhi Fuling Decoction combined with metronidazole on the level of the inflammatory factor CD138 in the treatment of endometritis and its improvement effect on the pregnancy rate. Methods A total of 50 patients with endometritis treated from March 2020 to March 2022 were selected and divided into an experimental group (treated with Guizhi Fuling Decoction combined with metronidazole) and a control group (treated with metronidazole alone) according to the treatment plan. The changes in the inflammatory factor CD138 before and after treatment were detected, and the improvement in the pregnancy rate was analyzed. Results The level of the inflammatory factor CD138 in the combined treatment group significantly decreased, and the pregnancy rate was significantly higher than that in the control group. Conclusion The treatment of endometritis with Guizhi Fuling Decoction combined with metronidazole can effectively reduce the CD138 level and improve the pregnancy rate of patients, which is worthy of clinical promotion.
Keywords: Guizhi fuling decoction; Metronidazole; Endometritis; Inflammatory factor; CD138; Pregnancy rate